Antibodies to inositol 1, 4, 5-triphosphate receptor 1 in patients with cerebellar disease. Issue 1 (January 2017) - Fouka, Penelope; Alexopoulos, Harry; Chatzi, Ioanna; Dedos, Skarlatos G.; Samiotaki, Martina; Panayotou, George; Politis, Panagiotis; Tzioufas, Athanasios; Dalakas, Marinos C.
Abstract : Objective: To describe newly identified autoantibodies associated with cerebellar disorders. Design/Methods: We first screened the sera of 15 patients with cerebellar ataxia, without any known associated autoantibodies, with immunocytochemistry on mouse brain. After characterization and validation of a newly identified antibody, 85 additional patients with suspected autoimmune cerebellar disease were screened using a cell-based assay. Results: Immunoglobulin G from one of the first 15 patients demonstrated a distinct staining pattern on Purkinje neurons. This autoantibody, as characterized further by immunoprecipitation and mass spectrometry, was binding inositol 1, 4, 5-triphosphate receptor 1 (IP3R1), an intracellular channel that mediates the release of Ca 2+ from intracellular stores. Anti-IP3R1 specificity was then validated with a cell-based assay. On this basis, screening of 85 other patients with cerebellar disease revealed 2 additional IP3R1-positive patients. All 3 patients presented with cerebellar ataxia; the first was eventually diagnosed with primary progressive multiple sclerosis, the second had a homozygous CAG insertion at the gene TBP, and the third was thought to have a neurodegenerative disease. Conclusions: We independently identified an autoantibody against IP3R1, a protein highly expressed in Purkinje neurons, confirming an earlier report. Because a mouse knockout model for IP3R1 exhibits ataxia and epilepsy, this autoantibody may have a functional role. The heterogeneity of the antibody-positive patients suggests that this antibody may either have a direct involvement in disease pathogenesis or it is a surrogate marker secondary to cerebellar injury. Anti-IP3R1 antibodies should be further explored in various ataxic and epileptic syndromes as they may denote a marker of response to immunotherapies.